Miejsce ewidencji pacjentów w systemie informacyjnym szpitala - Orliński, Ryszard (Patients’ records in the information system of a hospital, 2008)
The information system of hospitals is the source of information for the needs of efficient management. Information sources are created in different sub-systems where the most important on patients' record. The data taken from this system are fundamental in settling accounts with the National Health Fund and are fundamental in internal bookkeeping and financial accounts. At the same ü patient's record is a history of patient's health and grounds for medical procedures used in treatment.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 344-352